Impact Of Traditional Prognostic Factor And Chemotherapy Schedule Modification On Breast Cancer Patients: A 5 Year Retrospective Study In A District Specialist Hospital In The State Of Perak - Gunasekaran, Gobi Hariyanayagam (2021)
Chemotherapy schedule modifications are done in clinical practice due to treatment complications or the patients preference. Multiple clinical studies have established the negative prognostic impact of dose delay on survival rates. This study aims to investigate the prevalence and reason for chemotherapy schedule modification with the impact of schedule modification on the Overall Survival (OS) of the breast cancer patient. This retrospective cohort study was done among breast cancer patients receiving chemotherapy from 2013 to 2017 and was followed until 31 Dec 2018. Medical records of patients with cancer were reviewed. Inclusion criteria involved the female patients over eighteen years old, primary carcinoma of the breast, received Anthracycline or Taxane based chemotherapy regimen and completed more than two cycles of chemotherapy. Patients were categorised into three categories of no schedule modification, with schedule modification, and incomplete schedule. The Kaplan-Meier were used to test for survival differences in the univariate setting, and the Cox regression model was used in the multivariate setting. This study aims to measure the prevalence, OS rates, and Hazard Risk (HR) of these three treatment categories. Among 171 patients receiving chemotherapy, 28 (16.4%) had no schedule modification, 118 (69.0%) had schedule modification, and the remaining 25 (14.6%) had an incomplete schedule with OS of 75.0%, 59.3%, and 52.0%, respectively